1975
DOI: 10.1111/j.1540-4560.1975.tb01003.x
|View full text |Cite
|
Sign up to set email alerts
|

The Origins and Development of Concepts of Justice

Abstract: T h e origins anti development of concepts of justice are exaniinecl from three theoretical points of view-learning theory, psychoanalysis, and cognitive developmental theory. Cognitive developmental theory and research, particularly the work of Piaget and Kohlberg, has contributed most to our understanding of children's ideas o f justice and how these change and mature. Empirical data supporting the hypothesis that concepts o f justicedevelop through a fixed and invariant sequence of stages is reviewed togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Such turntaking strategies might reflect either an attempt to be numerically fair without knowing how to do the proper numerical calculation, or a different schema for fairness, in which fairness consists not of giving two recipients cardinally equivalent amounts, but rather taking turns such that everyone gets at least something (Frydman & Bryant, 1988). In support of the latter possibility, prior work suggests that young children do have different schemas of fairness than adults (e.g., Berg & Mussen, 1975;Chernyak & Sobel, 2016). Moreover, although age predicted children's references to fairness, it did not predict references to number, suggesting that the two schemas of sharing (one with reference to fairness and one with reference to number) may be qualitatively different and/or follow distinct developmental pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Such turntaking strategies might reflect either an attempt to be numerically fair without knowing how to do the proper numerical calculation, or a different schema for fairness, in which fairness consists not of giving two recipients cardinally equivalent amounts, but rather taking turns such that everyone gets at least something (Frydman & Bryant, 1988). In support of the latter possibility, prior work suggests that young children do have different schemas of fairness than adults (e.g., Berg & Mussen, 1975;Chernyak & Sobel, 2016). Moreover, although age predicted children's references to fairness, it did not predict references to number, suggesting that the two schemas of sharing (one with reference to fairness and one with reference to number) may be qualitatively different and/or follow distinct developmental pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that objective standards of what constitutes fairness are less important than what is perceived as being organizationally just (Beugre, 1998;Sheppard, Lewicki, & Minton, 1992). As Berg and Mussen (1975) note, the meaning of justice within an organization varies across indi-viduals. Similarly, a number of studies within the recruiting and job-choice literature have found that individual attributes affect how candidates react to different organizational characteristics (Barber, 1998).…”
Section: Hypothesismentioning
confidence: 99%